1986
DOI: 10.1111/j.1745-4557.1986.tb00802.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipids in Wild Ruminant Animals and Steers

Abstract: Lipid was extracted from the biceps femoris and longissimus dorsi muscles of pronghorn antelope, mule deer, elk, range steers and feedlot steers after being trimmed of subcutaneous fat and connective tissue. Muscles of game animals contained more phospholipids than those of steers and muscles of antelope and deer were higher in cholesterol. Muscles of feedlot steers contained the most total lipid and triglycerides. Polyunsaturated lipid was highest in muscles of game animals due to higher levels of phospholipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 17 publications
2
19
0
2
Order By: Relevance
“…From earlier studies of wild ruminants in Africa (Crawford & Gale, 1969 and in North America (Garton et al, 1971;Miller et al, 1986), it is apparent that inter-species differences exist in tissue lipid composition that probably result from interactions among differences in season and locale Rule & McCormick, 1998), gender (Garton et al, 1971), forage consumed Garton et al, 1971;Miller et al, 1986) and genetic constitution (Rule & McCormick 1998). Data from the present study indicated that the fatty acid composition of deer and antelope were generally more similar to one another for all four tissues studied than when compared to elk.…”
Section: Fatty Acid Comparisons Among Elk Deer and Antelopesupporting
confidence: 53%
See 2 more Smart Citations
“…From earlier studies of wild ruminants in Africa (Crawford & Gale, 1969 and in North America (Garton et al, 1971;Miller et al, 1986), it is apparent that inter-species differences exist in tissue lipid composition that probably result from interactions among differences in season and locale Rule & McCormick, 1998), gender (Garton et al, 1971), forage consumed Garton et al, 1971;Miller et al, 1986) and genetic constitution (Rule & McCormick 1998). Data from the present study indicated that the fatty acid composition of deer and antelope were generally more similar to one another for all four tissues studied than when compared to elk.…”
Section: Fatty Acid Comparisons Among Elk Deer and Antelopesupporting
confidence: 53%
“…The GC analysis revealed that elk tissue contained higher percentages of 16:1 n-7 and 18:1 n-7 and lower percentages of 18:1 n-9 and 18:0 in muscle, marrow and subcutaneous fat relative to deer and antelope. Other studies have also reported higher concentrations of 16:1 and lower concentrations of 18:1 in elk muscle (Miller et al, 1986) and subcutaneous fat (Garton et al, 1971) when compared to other species of North American ruminants. The reason for these differences is not entirely clear, but perhaps they are due to the fatty acid composition of preferred forage as well as genetic factors controlling lipogenic pathways in both liver and adipose tissue of elk.…”
Section: Fatty Acid Comparisons Among Elk Deer and Antelopementioning
confidence: 96%
See 1 more Smart Citation
“…Forrest et al (1979) e Pardi et al (1993) citam que o extrato etéreo é a fração de maior variação na composição da carne. Miller et al (1986) observaram que o aumento de gordura nos músculos é acompanhado pelo decréscimo de umidade. Resultado semelhante foi observado por Romanelli (1995) com dois grupos de jacaré-do-pantanal com pesos diferentes (75,23% de umidade; 5,32% de extrato etéreo, para animais de 16,5 a 20,9 kg; e 78,33% de umidade; 2,25% de extrato etéreo, para animais de 2,0 a 4,0 kg), sendo também observado no presente estudo.…”
Section: Resultsunclassified
“…Os dados obtidos foram analisados através do software estatístico SISVAR versão 4.0 (FERREIRA, 2000) com nível de significância de 5%, e quando apresentada diferença significativa aplicou-se o teste de Tukey. Miller et al (1986) observaram que o aumento de gordura nos músculos é acompanhado pelo decréscimo de umidade. Em jacaré, resultado semelhante foi relatado por Romanelli (1995) em animais de dois grupos de pesos diferentes; sendo 75,23% de umidade e 5,32% de extrato etéreo, para animais de 16,5 a 20,9 kg; e 78,33% de umidade; 2,25% de extrato etéreo, para animais de 2,0 a 4,0 kg.…”
Section: Methodsunclassified